Applied Sign Linguistics in the Global South and the Training of Libras L2 Teacher-Researchers in Brazil - Araújo, Paulo Jeferson Pilar; Costa, Alan Ricardo; Oliveira, Analú Fernandes de (The ESPecialist, 2024)
This research focuses on the emerging demands in the Global South broadly and in Brazil more specifically, regarding Applied Sign Linguistics (Linguística Aplicada das Línguas de Sinais, LALS, in Portuguese), considering the still nascent publications in Applied Sign Linguistics as defined by Napier and Leeson (2016). The objective is to examine how Applied Linguistics is incorporated into the curriculum of Libras (Brazilian Sign Language) programs and how the presence of issues specific to the field contributes to the consolidation of Brazilian Applied Sign Linguistics. In terms of methodology, with a qualitative approach, we chose documentary analysis (Paiva, 2019), specifically analyzing five Pedagogical Projects of Libras programs from federal universities recognized for their high quality by the Ministry of Education. From the conducted study, (i) gaps in curricula and Libras teacher training are discussed; (ii) it is argued that Libras, as a minoritized language, poses challenges to teacher education, and an advocated stance in Libras programs should be that of a professor-researcher; and (iii) a field of Applied Sign Linguistics sensitive to the context of Brazilian multilingualism is outlined, in synergy with a decolonial prism.